PERAN LEMBAGA PEMBERDAYAAN MASYARAKAT KELURAHAN (LPMK) DALAM MENINGKATKAN PEMBANGUNAN PARTISIPATIF DI KELURAHAN TALUN KECAMATAN SUMEDANG UTARA KABUPATEN SUMEDANG - Nadia Marsa Zahira (LPPM UNSAP, 2026)
The Village Community Empowerment Institution (LPMK) is an institution formed by the village to support community empowerment and strengthen citizen participation in the development process at the village level. This study aims to analyze the role of LPMK as a forum or community aspirations in development and a driver of community participation in Talun Village, North Sumedang District, Sumedang Regency using the theory of Sunyoto Usman (2004), which includes 4 main dimensions, namely: the role of LPM as a facilitator, the role of LPM as a mediator, the role of LPM as a motivator and the role of LPM as a dynamicator. The method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The technique for determining research informants is purposive sampling with informants consisting of the Village Head, Village Secretary, Head of Community Empowerment, Head of LPMK, and the community. Data collection techniques include literature studies and field studies through observation, interviews, and documentation. Data processing procedures include data reduction, data display, conclusion drawing/verification, and triangulation. The results of the study showed that LPMK was quite good at encouraging community participation through mentoring, development proposals, program supervision, and coordination with RT, RW, and sub-districts. The obstacles faced included budget limitations and low community understanding of self-reliance. Obstacles were overcome through fundraising, mutual cooperation, effective communication, and strengthening the role of LPMK in Musrenbang.